2019
DOI: 10.3390/ma12121936
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study on the Arsenate Adsorption Behavior of Calcium-Bearing Materials

Abstract: The calcium-bearing adsorbents are widely used in the treatment of arsenic-containing wastewater due to their excellent treatment effect and economy. In order to obtain high-efficient adsorbents for arsenate (As(V)) removal, the adsorption behavior of calcium oxide (CaO), calcium fluoride (CaF2) and calcium carbonate (CaCO3) on As(V) in aqueous solution at different concentrations were explored. The adsorption mechanism was also explored based on surface characteristics: morphology, specific surface area, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Wang and Zhu 2019 [ 42 ] studied the removal of As(V) ions from aqueous solutions using CaO, CaF 2 and CaCO 3 ; they found that the main mechanism for the removal of As(V) ions by calcium-bearing materials was the formation of insoluble calcium arsenate salt generated by arsenate anions and calcium ions. Ayala and Fernandez 2020 [ 43 ] studied the capacity of four industrial waste materials originating from steelmaking processes (slags) and from gas treatment at a thermal power plant (fly ash and gypsum) to remove As ions from a leachate from the spoil heap of an abandoned mercury mine.…”
Section: Resultsmentioning
confidence: 99%
“…Wang and Zhu 2019 [ 42 ] studied the removal of As(V) ions from aqueous solutions using CaO, CaF 2 and CaCO 3 ; they found that the main mechanism for the removal of As(V) ions by calcium-bearing materials was the formation of insoluble calcium arsenate salt generated by arsenate anions and calcium ions. Ayala and Fernandez 2020 [ 43 ] studied the capacity of four industrial waste materials originating from steelmaking processes (slags) and from gas treatment at a thermal power plant (fly ash and gypsum) to remove As ions from a leachate from the spoil heap of an abandoned mercury mine.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, many researchers have found that the presence of Ca 2+ promotes the removal of arsenic through the formation of Ca-As sediments (Zama et al, 2022). The mechanism of arsenic removal by lime (CaO) and hydrated lime (Ca (OH) 2 ) has been proved to be through the precipitation of different types of calcium arsenate salts (Yang et al, 2021;Zama et al, 2022) and CaO, which may form calcium arsenate precipitation in the process of As(III) removal, thus improving the As(III) adsorption efficiency of FMBO/OS (Mollah et al, 2004;Wang & Zhu, 2019). The FMBO/OS after As(III) adsorption was analyzed by XRD, as shown in Figure 7, which confirmed that Ca-As sediments, CaHAsO 4 Á3H 2 O (d = 4.96, 2.95, 2.63, and 2.51 Å), Ca(H 2 AsO 4 ) 2 (d = 3.04, 1.79 and 1.48 Å), and CaAs 2 O 6 (d = 2.94 and 2.96 Å) had formed (Mollah et al, 2004).…”
Section: Mechanism Of Removal Of As(iii) By Fmbo/osmentioning
confidence: 99%